Canadian natural science graduate stipends lie below the poverty line - Andrew J. Fraass; Thomas J. Bailey; Kayona Karunakumar; Andrea E. Wishart (PLoS ONE, 2025)
Despite the critical role of graduate students in the Canadian research ecosystem, students report high levels of financial stress. As a case study, we collected graduate minimum stipends and tuition data from all university graduate programs in Canada in Ecological Sciences/Biology and Physics, along with cost of living measures for the cities in which they reside. These data are heterogeneous, complex, and in many cases simply not publicly available, making it challenging for potential graduate students to understand what support they should expect. We find Canadian minimum stipends are at values almost exclusively below the poverty threshold. Only two of 140 degree programs offered stipends which meet cost of living measures after subtracting tuition and fees. For graduate programs which offered a minimum guaranteed stipend, the average minimum domestic stipend is short ~Can$9,584 (international ~Can$16,953) of the poverty threshold after accounting for payment of tuition and fees. On average, approximately 33% of a minimum stipend is returned to the university in tuition and fees by a domestic Canadian student and 76% (59% median) by an international student, though there are important caveats with the international student comparison. While international comparison is difficult, the highest Canadian minimum stipend found is roughly equivalent or lower than the lowest stipend within the largest dataset of United States of America (US) Biology stipends, and lower than the United Kingdom (UK) stipend. University endowment correlates with minimum stipend amount but intra- and inter-institutional differences suggest it is not solely institutional wealth associated with graduate pay. We observe Canada is behind comparable countries in minimum funding levels for the next generation of scientists.